Co-prescribing Naloxone with Opioids in the Emergency Department - Weis, Mackenzie (My University, 2019)
Background: The United States is facing an opioid epidemic with 115 Americans dying every day from opioid overdoses and they are the leading cause of accidental death. Naloxone (Narcan) is an opioid antagonist, which reverses respiratory depression caused by opioid overdoses. The World Health Organization now recommends Naloxone as a strategy to reduce overdose deaths. Purpose: The purpose of this project was for 75% of providers in the Emergency Department (ED) at the project site to co-prescribe Naloxone when discharging patients home with opioids. Methods: A site-wide protocol was created for providers in collaboration with the organization’s opioid task force. This protocol was implemented in the ED following educational in-services to providers to revise the Best Practice Advisory (BPA) opioid order set to alert providers. Lastly, chart reviews were conducted to determine changes of providers’ co-prescribing Naloxone rates. Results: Fifteen (20%) of providers in the ED attended the educational in-services. Chart reviews (n=324) showed a 40% increase in co-prescribing Naloxone within the ED among providers’ trained. Issues pertaining to overridden and canceled BPAs were discovered identifying technology issues resulting in provider desensitization of the BPAs in addition to ethical concerns. Implications for Practice: Preliminary results suggest that provider training increases co-prescribing Naloxone rates in the ED. It is recommended that leadership consider comprehensive efforts to decrease opioid-induced deaths with the widespread distribution of Naloxone that will help diminish opioid overdose fatalities.
Keywords: Opioid abuse, co-prescribing Naloxone, provider education, protocol integration, Emergency Department